PENGARUH KOMPETENSI SUMBER DAYA MANUSIA DAN GAYA KEPEMIMPINAN TERHADAP KUALITAS LAPORAN KEUANGAN DESA DI DESA KECAMATAN KALIPURO - Moh Mujib (Accounting Journal of Ibrahimy (AJI), 2025)
This study aimed to determine: (1) The Influence of Human Resource Competence on the Quality of Village Financial Reports in Kalipuro District. (2) Leadership Style on the Quality of Village Financial Reports in Kalipuro District. This study was descriptive using quantitative data analysis with a causal research design. The data used in this study are primary data in the form of questionnaires distributed in villages in Kalipuro District. The population in this study was 50 people and the number of samples was 40 people. Data analysis was carried out using multiple linear regression methods with the help of SPSS software version 21. This study used 2 independent variables, namely Human Resource Competence (X1), Leadership Style (X2) and Financial Report Quality (Y) as the dependent variables. The results of this study indicated that Human Resource Competence affects the quality of village financial reports in Kalipuro District. Leadership style affects the quality of village financial reports in Kalipuro District.